Biomechanical Considerations of Patching Material for Posterior Scleral Reinforcement Surgery - Ma, Jinlei; Wu, Fangyuan; Liu, Zhiyong; Fang, Yijiong; Chu, Xu; Zheng, Linyan; Xue, Anquan; Nan, Kaihui; Qu, Jia; Cheng, Lingyun (Frontiers in Medicine, 2022)
Purpose: To characterize biomechanical properties of genipin-crosslinked human dura mater as reinforcing material for posterior scleral reinforcement (PSR) and to compare it with crosslinked human sclera. Methods: Donor dura mater and sclera were crosslinked in the same optimized genipin solution. Resistance to enzyme degradation for both materials were investigated by exposing the materials to accelerated enzyme degrading. Elastic modulus and tensile strength were measured by biomechanics testing equipment. Crosslinked human dura mater was used as reinforcing patch in PSR on 57 adult pathologic myopic eyes. The patients were followed up for an average 3 years. The main outcome was eye globe axial length change and safety profile of the reinforcing material. Results: Crosslinked dura mater demonstrated similar percentage wise weight loss to crosslinked sclera when exposed to enzymatic solution. Dura mater has higher density than sclera. The retaining elastic modulus after enzyme exposure was 72.02 MPa for crosslinked dura mater while 53.88 MPa for crosslinked sclera, 34% greater for crosslinked dura mater, p=0.0186). At the end of 3 years follow-up, the mean globe axis of the surgery eyes was reduced by 1.29 mm (from 30.81 to29.51 mm, p<0.0001, paired t-test). Visual acuity (BCVA logMar) improved by 0.10 logMar unit which is an improvement of 5 letters (p=0.0184, paired t-test). No material specific complication was noted. Conclusion: Crosslinked human dura mater may be superior to crosslinked human sclera as reinforcing material for PSR to manage progression of high myopia. This material was well tolerated on human eye.